USING THE GINI COEFFICIENT TO BUILD A CREDITSCORING MODEL - Sultanova, N.; Tulegenova, A.; Suleimen, B. (Journal of Emerging Technologies and Computing, 2024)
The credit scoring model is widely used to predict the likelihood of a customer default. To measure the quality of such scoring models, you can use quantitative indicators such as the GINI index, KolmogorovSmirnov (KS) statistics, Lift, Mahalanobis distance, information statistics. This article discusses and illustrates the practical use of the GINI index.